A two-stage cognitive theory of the positive symptoms of psychosis. Highlighting the role of lowered decision thresholds. (September 2017) - Moritz, Steffen; Pfuhl, Gerit; Lüdtke, Thies; Menon, Mahesh; Balzan, Ryan P.; Andreou, Christina
Abstract: Objectives: We outline a two-stage heuristic account for the pathogenesis of the positive symptoms of psychosis. Methods: A narrative review on the empirical evidence of the liberal acceptance (LA) account of positive symptoms is presented. Hypothesis: At the heart of our theory is the idea that psychosis is characterized by a lowered decision threshold, which results in the premature acceptance of hypotheses that a nonpsychotic individual would reject. Once the hypothesis is judged as valid, counterevidence is not sought anymore due to a bias against disconfirmatory evidence as well as confirmation biases, consolidating the false hypothesis. As a result of LA, confidence in errors is enhanced relative to controls. Subjective probabilities are initially low for hypotheses in individuals with delusions, and delusional ideas at stage 1 (belief formation) are often fragile. In the course of the second stage (belief maintenance), fleeting delusional ideas evolve into fixed false beliefs, particularly if the delusional idea is congruent with the emotional state and provides "meaning". LA may also contribute to hallucinations through a misattribution of (partially) normal sensory phenomena. Interventions such as metacognitive training that aim to "plant the seeds of doubt" decrease positive symptoms by encouraging individuals to seek more information and to attenuate confidence. The effect of antipsychotic medication is explained by its doubt-inducing properties. Limitations: The model needs to be confirmed by longitudinal designs that allow an examination of causal relationships. Evidence is currently weak for hallucinations. Conclusions: The theory may account for positive symptoms in a subgroup of patients. Future directions are outlined. Highlights: A two-stage heuristic account for the pathogenesis of positive symptoms is presented. Patients with psychosis have a lowered decision threshold. Due to liberal acceptance confidence in errors is enhanced relative to controls. Fixed delusions emerge if the delusional idea provides "meaning".